Syariah Compliance Stock: Current Issues and The Way Forward - M. Yazid Afandi (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2016)
Shariah compliance stock shows promising growth in Islamic finance industrty in the last three decades. It can be seen from the number of company listed in the Islamic capital market, issued by shariah committe. To be categorized as shariah compliance stock, stock screening will be conducted in ensuring that all company activities comply to shariah standard. The objective of this paper is to describe the shariah standar of stock screening in accordance with fiqh concept. In addition, this paper also illusterate some practice of stock screening in many countries. By conducting library research, this study found that shariah standard applied in stock screening is fully based on shariah and doesnt contravene with fiqh concept. Moreover, the practice of stock screening, still shows some differences which is affected by the difference of Islamic finance model.